Giant vesical calculus with its complications: The first case to be reported in an adolescent female - Gangwar, Pradeepika; Singh, Pushpendra; -, Reena; Agrawal, Shweta (Indian Journal of Case Reports, 2020)
Urinary bladder stones weighing more than 100 g are considered giant. Here, we are reporting a case of giant vesical calculus weighing 1050 g in an adolescent female presenting with lower urinary tract symptoms and renal insufficiency. Giant vesical calculus is reported in the middle to old age, more commonly in male patients.